ANALISIS PERKEMBANGAN PASARAN SAHAM ISLAM DI MALAYSIA - Mohd Hussin, Mohd Yahya; Borhan, Joni Tamkin (Jurnal Syariah, 2009)
Islamic stock market (ISM) is one of the most important components in the Islamic capital market (ICM). In making ISM more competitive, Syariah Advisory Committee of Security Commission has introduced the listing of Syariah approved counter/stock based on the primary sources (al-Quran & al-Sunnah) and other supporting sources with agreed research method. It serves as a guide to people involved in Islamic investment field. Consequently, the number of Syariah approved counter/stock covered almost 87 percent of the total listed counter/stock at Kuala Lumpur Stock Exchange (KLSE) in 2008, accounting for 60 percent of the entire Malaysia stock exchange by market capitalization.